International Seminar on Contemporary Fiqh: issues and challenges (SCF2012) - Kayadibi, Saim (Mehir Vakfi, 2013)
The seminar, organized by the Department of Fiqh and Usul al-Fiqh, Faculty of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia (IIUM), was held on 18-19 December 2012 at the Banquet Hall in IIUM, Kuala Lumpur, Malaysia. The 200 delegates from different continents including Asia, Europe, Africa, Middle East participated and 48 of them were paper presenters apart from two very well-received Keynote Speakers,Mohd Daud Bakar (Chairman, Shariah Advisory Council, Bank Negara Malaysia[BNM]), Fatris Bakaram (Mufti of Singapore), and opening speech was given by Mohd Puad Zarkashi (Deputy Education Minister of Malaysia), as well as media outlets and respectable number of public and government representatives, religious officers, and academics from prestigious international universities also participated in the Conference.